2022
DOI: 10.1038/s41420-022-01073-7
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib inhibits LPS-induced inflammation by regulating Lyn-MAPK-NF-kB/AP-1 pathway and TLR4 expression

Abstract: Sorafenib is an anti-tumor drug widely used in clinical treatment, which can inhibit tyrosine kinase receptor on cell surface and serine/threonine kinase in downstream Ras/MAPK cascade signaling pathway of cells. Tyrosine kinase phosphorylation plays an important role in inflammatory mechanism, such as TLR4 tyrosine phosphorylation, MAPK pathway protein activation, and activation of downstream NF-кB. However, the effects of sorafenib on LPS-induced inflammatory reaction and its specific mechanism have still re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Interestingly, complex connections exist between the NF-kB signal transduction pathway and many biochemical pathways. 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, complex connections exist between the NF-kB signal transduction pathway and many biochemical pathways. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, complex connections exist between the NF-kB signal transduction pathway and many biochemical pathways. 24 Janus kinase/signal transducer activator of transcription factor (JAK/STAT), as well as the mitogen-activated protein kinase/extracellular signal-regulated kinase (MAPK/ ERK), Wnt/β-catenin are a number of molecular cellular pathways that are essential for the development, growth, and metastasis of HCC tumors. 25 Liver cancer, typically activates the MAPK/ERK signaling cascade.…”
Section: Discussionmentioning
confidence: 99%
“…MEK and IKKα, which activates NFkB signalling, were shown to be downstream targets of LYN in an analysis of the kinomes of imatinib-sensitive and resistant leukaemia cells (Cooper et al, 2013). LYN is required for TLR2-mediated NFkB activation though PI3K signalling in HEK293 cells engineered to express TLR2 (Toubiana et al, 2015) while TLR4-mediated NFkB activation in macrophages as a response to LPS treatment is associated with LYN activation and subsequent activation of downstream MAP pathways (Li et al, 2022). Furthermore, Lyn -/- mast cells show less MAPK and IkB phosphorylation and less NFkB nuclear translocation after TLR4 triggering than wild type cells (Avila et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…25−27 On the other hand, Sorafenib is a multiple kinase inhibitor, with action in the Raf/MEK/ERK signaling pathway; more recently, its antiinflammatory effects have also been proposed. 28,29 All inhibitors described above have the potential to be effective against the consequences of cytokine storm typically observed in SARS-CoV-2 infections. Although some of them have been tested in clinical trials for COVID-19 treatment due to their reported anti-inflammatory activities, none were evaluated as potential SARS-CoV-2 MPro inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials are evaluating the potential of kinases inhibitors in COVID-19 treatment. , The promising compounds in clinic to treat the inflammatory phase of COVID-19 are JAK-inhibitorsBaricitinib, Ruxolitinib, and Tofacitinib being well known for their anti-inflammatories activities. MAPK are responsible for regulating inflammatory responses in mammalian cells, consisting of p38, extracellular signal-regulated kinase (ERK), and c-Jun NH2-terminal kinase (JNK) . Compounds BIRB-796 (Doramapimod) and Skepinone-L are p38 MAPK inhibitors with potential to treat several types of cancer, as well as inflammatory chronic diseases. On the other hand, Sorafenib is a multiple kinase inhibitor, with action in the Raf/MEK/ERK signaling pathway; more recently, its anti-inflammatory effects have also been proposed. , All inhibitors described above have the potential to be effective against the consequences of cytokine storm typically observed in SARS-CoV-2 infections. Although some of them have been tested in clinical trials for COVID-19 treatment due to their reported anti-inflammatory activities, none were evaluated as potential SARS-CoV-2 MPro inhibitors.…”
Section: Introductionmentioning
confidence: 99%